An Empirical Analysis of the Determinants of Corporate Crime in Malaysia - Mung, Ling Voon; Voon, Sze-Ling; Puah, Chin-Hong (Universiti Putra Malaysia, 2008)
Corporate crime is not new in Malaysia. Each year the cases reported have increased dramatically. The phenomenon will undermine the confidence of both existing and potential investors. In this study, we aim to investigate the determinants of corporate crime activities in organizations, in order to minimize the occurrence of fraud. A survey involving existing and potential investors was undertaken. The findings indicate that the corporate crime determinants ranked by most of the respondents are insufficient controls, followed by personal financial pressure and expensive lifestyle. To minimize the occurrence of corporate crime activities in the organizations, the management team should impose tighter control over internal operations.